Analysis of the Grid Sampling Method for Noise Mapping - Valentın GÓMEZ ESCOBAR; Juan Miguel BARRIGÓN MORILLAS; Guillermo REY GOZALO; Rosendo VILCHEZ-GÓMEZ; Javier CARMONA del RIO; Juan A. MENDEZ SIERRA (Archives of Acoustics, 2013)
The grid method is the most widely used technique for measurement-based noise assessment, and indeed is part of the ISO 1996-2 standard. Nevertheless it has certain disadvantages. The present work is an analysis of the grid method for evaluating noise, firstly in the city of C´aceres and, secondly in two other smaller towns. Using as reference a 200 metre grid study, a study was made of the effect of varying the size and form of the grid on the city’s overall noise value, the percentage of data found to lie above some reference thresholds, and the noise value assigned to a certain zone of the city. The ISO 1996 recommendations of the necessity of new sampling points and the method’s predictive capacity for these new measurements were also analyzed.